Mesenchymal Stem Cells in Periodontal Regeneration: A Review - Nikita Samal1 , Gatha Mohanty2 , Rinkee Mohanty,3 Rashmita Nayak4 , Anurag Satpathy4 , Abhaya Chandr (Institute of Medico-legal Publications Pvt Ltd, 2020)
Periodontitis is most predominantly marked and plays a vital burden in dental health as well as in systemichealth. It starts from a phase of swelling on supporting structures of tooth thereafter proceeds, destructionof tissues up till damage to tooth arises. Reconstruction of defective supporting tissues in periodontiuminclusive of cementum, pdl and alveolar bone is a challenging objective in periodontal regeneration therapythat can adequately diminish periodontitis caused tooth loss. In the regeneration of tooth and their supportingstructures that are gone or damaged due to periodontal disease, stem cells perform an essential character.Here we talk about the primary information based on periodontal tissue regeneration using mesenchymalmother cells.